Lysosome biogenesis: Regulation and functions - Yang, Chonglin (J Cell Biol, 2021)
Lysosomes are degradation centers and signaling hubs in cells and play important roles in cellular homeostasis, development, and aging. Changes in lysosome function are essential to support cellular adaptation to multiple signals and stimuli. Therefore, lysosome biogenesis and activity are regulated by a wide variety of intra- and extracellular cues. Here, we summarize current knowledge of the regulatory mechanisms of lysosome biogenesis, including synthesis of lysosomal proteins and their delivery via the endosome–lysosome pathway, reformation of lysosomes from degradative vesicles, and transcriptional regulation of lysosomal genes. We survey the regulation of lysosome biogenesis in response to nutrient and nonnutrient signals, the cell cycle, stem cell quiescence, and cell fate determination. Finally, we discuss lysosome biogenesis and functions in the context of organismal development and aging.